STUDI PADA PROSES PEMBUANGAN KAPUR (DELIMING) KULIT KAMBING MENGGUNAKAN GAS CO2 - Prasetyo Hermawan; Alfani Risman Nugroho (Politeknik ATK Yogyakarta, 2019)
This purpose of this research was to study the use of CO2 gas as an alternative material for deliming pelt of goat skin. In a glass reactor with a volume of 1 liter flowing with CO2 gas in varied flow, ie; 0, 10, 25 and 50 cc / minute. The float used is 200% based of the weight of the skin, then the data is taken from the liquid and the skin. The initial pH of lime water is 11.8 and after 30 minutes of CO2 gas flowing with a discharge of 25 cc/ min, the pH of lime water drops to 6.71 and after 60 minutes it became 6.39. Deliming liquid had an initial pH of 7.17 and a final pH without gas flow is 11.34, while the CO2 gas discharge was 25 cc/min the pH becomes 6.51. The TDS and conductivity of deliming liquid decreases when the CO2 gas discharge was raised, the final TDS at the CO2 gas discharge of 25 cc/min is 4354 ppm, while the final conductivity is 8798 µC/cm. The biggest compressibility of goat skin was in the flow of CO2 gas with a debit of 10 cc/minute, which was 16,71%. At the end of the deliming with CO2 gas discharged of 25 cc/min, the COD value increased by 47.1% to 3137 mg/l and the calcium content raised to 1.015%.